1978
DOI: 10.1128/jvi.27.3.475-482.1978
|View full text |Cite
|
Sign up to set email alerts
|

Effects of adenine arabinoside on lymphocytes infected with Epstein-Barr virus

Abstract: Low concentrations of adenine arabinoside inhibited growth of two Epstein-Barr virus producer cell lines in culture, while not significantly affecting a nonproducer cell line and a B-cell-negative line. These observations were extended to include freshly infected cells. Mitogen-stimulated human umbilical cord blood lymphocytes were unaffected by the drug at concentration levels that inhibited [3H]thymidine incorporation into the DNA of Epstein-Barr virus-stimulated cells. DNA synthesis in Epstein-Barr virus-su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1979
1979
1999
1999

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Concentrations of 20 and 100 ng/ml (sufficient to inhibit replication of covalently closed supercoiled plasmids [6,11,17]) inhibited EBV DNA synthesis at the 10 to 17% level. It has previously been shown that inhibition of EBV DNA synthesis leads to a decline in VCA production (4,5,7,14,18). The percentage of cells in the P3HR-1 producer cell line expressing VCA declined with increasing concentration of ethidium bromide proportionately to the observed inhibition of DNA synthesis; i.e., 500 ng of ethidium bromide per ml yielded a 50% inhibition of both DNA and VCA production.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Concentrations of 20 and 100 ng/ml (sufficient to inhibit replication of covalently closed supercoiled plasmids [6,11,17]) inhibited EBV DNA synthesis at the 10 to 17% level. It has previously been shown that inhibition of EBV DNA synthesis leads to a decline in VCA production (4,5,7,14,18). The percentage of cells in the P3HR-1 producer cell line expressing VCA declined with increasing concentration of ethidium bromide proportionately to the observed inhibition of DNA synthesis; i.e., 500 ng of ethidium bromide per ml yielded a 50% inhibition of both DNA and VCA production.…”
Section: Resultsmentioning
confidence: 92%
“…x 10' cells/ml. The infection was allowed to proceed at 350C for an additional 4 h, after which the cells were pelleted, washed twice in phosphate-free minimal essential medium, and then suspended in phosphatefree minimal essential medium containing 1% heatinactivated (dialyzed) fetal calf serum to a concentration of 5 x 105 to 1 x 106 cells/ml. At this time [methyl-3H]thymidine (Schwarz/Mann; 18 Ci/mmol) was added as indicated (see figure legends).…”
Section: Crude Virus Preparation Cells and Large Debrismentioning
confidence: 99%
“…The cells were maintained in RPMI 1640 medium containing 10% fetal bovine serum with 100 U of penicillin per ml, 100 U of streptomycin per ml, 2.5 g of amphotericin B per ml, and 2 mM glutamine at 37°C in a humidified atmosphere with 5% CO 2 . Raji and B95-8 cells show a lag in growth for approximately 24 h after splitting, followed by exponential growth peaking at 5 days and, finally, a subsequent decrease in the cell count (4,5). For these studies two subpopulations of Raji and X50-7 cells were maintained in 25-cm 2 flasks for at least 2 weeks prior to chemical induction: cultures designated fast growing were split 1:1 with fresh medium twice per week (1st and 4th days), and cultures designated slow growing were split 1:1 with fresh medium once per week.…”
Section: Methodsmentioning
confidence: 99%
“…Compounds that inhibit replication of EBV in vitro include adenine arabinoside (3,11), phosphonoformic acid, and phosphonoacetate (16,60,63,77), a class of halogenated nucleoside analogs exemplified by FIAC [1-(2-fluoro-2-deoxy-␤-D-arabinofuranosyl)-5-iodocytosine] (42,46), BVDU [E-5-(2-bromovinyl)-2Ј-deoxyuridine) (43,44), ganciclovir (39), acyclovir (ACV) (12,24,45), and the phosphonated nucleoside analogs HPMPC {(S)-1-[(3-hydroxy-2-phosphonylmethoxy)propyl]cytosine} and related compounds (40,41). Nucleoside analogs and the pyrophosphate analogs phosphonoformic acid and phosphonoacetate inhibit replication of most or all of the herpesviruses.…”
mentioning
confidence: 99%